Hermeneutics As al-Dakhîl: Criticism of Abdullah Saeed's Thinking on The Crucifixion of Isa al-Masih - Abd Muin (Jurnal Ushuluddin, 2022)
Entering the modern period of discourse on the interpretation of the Koran, the emergence of a new approach to interpreting the Koran, namely the hermeneutical approach, has sparked much debate. When applied to it in general, the polemic circle around hermeneutics revolves around the question of the validity of hermeneutic methodology to the Koran and the analysis of the results of the interpretation of hermeneutic applications to the Koran, which distort the fundamental teachings of Islam. Very few studies have criticized the results of implementing the hermeneutics of the Koran using the theoretical framework of al-dakhīl fi al-Tafsīr. So, this research aims to fill this void. The author's research criticizes Abdullah Saeed's thoughts about the crucifixion of Isa al-Masih as a result of using the hermeneutic method of contextual interpretation. Through the methodology of content analysis and critical analysis, the authors found. First, Abdullah Saeed, through his theory of contextual interpretation, interprets verse 157 of al-Nisa with the conclusion that Isa al-Masih was killed and crucified. Second, Abdullah Saeed's interpretation is identified as al-dakhīl because Abdullah Saeed interprets the Koran out of the meaning of the text without any guidance; even the clues from the series of verses 157-159 require the textual meaning. In addition, forcing a uniform understanding of the crucifixion of Isa al-Masih against Christian traditions has violated the principle of religious pluralism